Netitnaginių uolienų apdirbimo technologijos ir dirbinių gamyba finaliniame paleolite–mezolite Lietuvoje - Rimkutė, Gabrielė (Archaeologia Lituana, 2012)
Uolienų apdirbimas yra ankstyviausia ir ilgiausiai kada nors taikyta technologija, kurios raidą jau daug metų bando analizuoti visų šalių archeologai, taip pat ir Lietuvos akmens amžiaus tyrėjai. Deja, mūsų šalies finalinio paleolito–mezolito laikotarpiai rekonstruojami remiantis vien titnago uolienos apdirbimo technologijų nagrinėjimu. Kitos uolienos tampa tyrimų objektu tik analizuojant neolitą ar vėlesnius laikus. ... NON-FLINT RAW MATERIAL MANUFACTURE TECHNOLOGIES AND TOOL MAKING TECHNOLOGIES IN FINAL PALAEOLITHIC–MESOLITHIC LITHUANIA Gabrielė Rimkutė Summary The investigation of non-flint raw material artefacts of Final Palaeolithic–Mesolithic period was a topic that Lithuanian archaeologists did not pay a lot of attention to. For many years this group of finds was ignored or hardly recognised during the excavations. The lack of information published and an obscure number of raw material artefacts in the museum collections of Lithuania has led to collect all the probable raw material artefacts altogether and to obtain as much information as these finds could actually provide. All types of artefacts were analyzed, meaning raw material knapping assemblage and the definite implements. After a careful research of the collections of finds in the museums and newest data of recent excavations, more than 1 500 artefacts were chosen up, added to the database, and were examined on different aspects. The types of raw material used were determined with a help of geologists from Vilnius University. Each artefact was described according to its general size measurements and a possible shaping work done on it. ...